Learn to forget: Does post-exposure administration of d-cycloserine enhance fear extinction in agoraphobia?. (October 2018) - Pyrkosch, L.; Mumm, J.; Alt, I.; Fehm, L.; Fydrich, T.; Plag, J.; Ströhle, A.
Abstract: The use of d-cycloserine (DCS) to augment exposure based therapy for anxiety disorders has shown mixed, although overall positive effects. Aim of the present study was to examine post-exposure administration of DCS in patients with agoraphobia with or without panic disorder. 73 patients with agoraphobia (with or without panic disorder) were treated with 12 sessions of cognitive behavioral therapy (CBT) including 3 exposures. Following successful exposure patients were given double blind either placebo or 50 mg of DCS. Primary outcome criterion was change in the Panic and Agoraphobia Scale (PAS) between CBT session t1, t4 (+∼2 months), t10 (+∼3 months) und t11 (+∼4 months). During the course of CBT the patients' symptomatology decreased significantly as measured by primary and secondary outcome criteria, however, without an additional benefit for DCS treated patients. Exploratory sub-group analyses for severely ill patients and patients with high anxiety and strong habituation during exposure showed that DCS administration was associated with increased improvement during the 1-month follow-up period (t10 - t11) with medium to large effect sizes (range in effect size η 2 p from .06 to .25). Our study results are consistent with recent research on DCS, indicating a beneficial augmentative effect for sub-groups of anxiety patients. The lack of an overall DCS effect for the whole patient sample might be explained by a dual mechanism in fear conditioning and extinction with different cognitive processes being involved during exposure depending on the degree of anxiety experienced by the patient. Highlights: Post-exposure administration with DCS did not enhance CBT in patients with agoraphobia. DCS was not associated with more improvement in variables associated with agoraphobia. Severely ill patients treated with DCS compared to Placebo improved more during follow-up. Patients with high anxiety during exposures treated with DCS improved more during follow-up. Patients with strong habituation during exposures treated with DCS improved more during follow-up.